2007
DOI: 10.1111/j.1365-3083.2007.02038.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human TIM‐1 and TIM‐3 on Lymphocytes from Systemic Lupus Erythematosus Patients

Abstract: The T‐cell immunoglobulin‐ and mucin‐domain‐containing molecules (TIMs) comprise a new family of cell surface molecules expressed on T cells. TIM‐3 is expressed on T helper type 1 (Th1) cells and implicated in the pathogenesis of Th1‐driven auto‐ and allo‐immune diseases. TIM‐1 is suggested to act as a co‐stimulatory molecule for all T cells, but with potentially stronger effects on Th2 than Th1 cells and is associated with Th2‐related immune diseases. However, the TIM molecules have not been investigated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 30 publications
(56 reference statements)
3
46
1
2
Order By: Relevance
“…22 In a previous report, increased levels of Tim-1 were detected in SLE patients, which correlated with IL-10 expression. 40 However, we failed to detect any significant difference in Tim-1 mRNA levels in PBMCs from SLE patients versus healthy controls. This discrepancy may be due to differences in the SLEDAI of patients involved in each study: in the previous report, 17 out of 19 SLE patients had a SLEDAI higher than 5, while in the present study most patients (19/25) had a SLEDAI lower than 5.…”
Section: Discussionmentioning
confidence: 58%
“…22 In a previous report, increased levels of Tim-1 were detected in SLE patients, which correlated with IL-10 expression. 40 However, we failed to detect any significant difference in Tim-1 mRNA levels in PBMCs from SLE patients versus healthy controls. This discrepancy may be due to differences in the SLEDAI of patients involved in each study: in the previous report, 17 out of 19 SLE patients had a SLEDAI higher than 5, while in the present study most patients (19/25) had a SLEDAI lower than 5.…”
Section: Discussionmentioning
confidence: 58%
“…92 In another study, TIM-1 expression on peripheral blood mononuclear cells from SLE patients (associated with Th2 responses) correlated significantly with disease activity whereas TIM-3 expression (associated with Th1 responses) did not. 93 …”
Section: Sle: Acute Antibody-mediated Diseasementioning
confidence: 99%
“…T cell immunoglobulin-and mucin-domain-containing molecule-3 (Tim-3) plays a pivotal role in immune regulation and tolerance induction [11][12][13][14][15][16][17][18][19][20][21][22][23]. Engagement of Tim-3 by galectin-9 negatively regulates IFN-c secretion and influences the ability to induce T cell tolerance in both mice and humans [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Engagement of Tim-3 by galectin-9 negatively regulates IFN-c secretion and influences the ability to induce T cell tolerance in both mice and humans [14,16]. Recent studies have shown that Tim-3 is differentially expressed in innate versus adaptive immune cells, and that the ligation of Tim-3 can induce distinct signaling events, which may influence a range of inflammatory conditions [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%